A Drosophila mutation that eliminates a calcium-dependent potassium current. - Elkins, T (1986)
A mutation of Drosophila, slowpoke (slo), specifically abolishes a Ca2+-dependent K+ current, IC, from dorsal longitudinal flight muscles of adult flies. Other K+ currents remain normal, providing evidence that IC is mediated by a molecularly distinguishable set of channels. The pharmacological properties of IC are similar to those of Ca2+-dependent currents in some vertebrate cells. The muscle action potential was significantly lengthened in slo flies, indicating that IC plays the major role in its repolarization.